Confirmatory factor analysis model of agile leadership for school administrations in secondary level under the local administrative organization - Ritthichai Wisetchat; Piangkae Poophayang; Sirisak Ardwichai (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
This study aimed to examine and validate the structural components of agile leadership among secondary school administrators under local administrative organizations. The sample consisted of 286 administrators and teachers selected through multi-stage sampling to ensure representation across school contexts. A five-point Likert scale questionnaire with high reliability (α = 0.962) was employed, and data were analyzed using descriptive statistics and first-order confirmatory factor analysis (CFA). The findings revealed that all five components of agile leadership were rated at a very high level, arranged alphabetically as follows: adaptation, collaboration, flexibility, learning orientation, and team management. The CFA results indicated that the proposed measurement model demonstrated an excellent fit with the empirical data (χ² = 7.041, χ²/df = 1.760, df = 4, p = 0.134, AGFI = 0.964, CFI = 0.998, NFI = 0.995, RMR = 0.005, RMSEA = 0.052). These results confirm the construct validity of agile leadership as a multidimensional competency essential for administrators operating in dynamic and complex educational environments and provide a validated framework to inform leadership development and policy implementation.